The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00277-017-3103-x
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging results with the compassionate use of hydralazine/valproate (TRANSKRIP™) as epigenetic treatment for myelodysplastic syndrome (MDS)

Abstract: The hypomethylating agents azacytidine and decitabine are unaffordable for many patients with MDS. The combination of the DNA methyltransferase inhibitor hydralazine and the histone deacetylase inhibitor valproate has shown preliminary efficacy in MDS. The aim of this study is to evaluate the clinical efficacy and safety of hydralazine/valproate in a case series of MDS patients treated in a compassionate manner. Hydralazine was dosed according to the acetylation genotype of patients (slow acetylators 83 mg dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…A therapeutic significance of HDZ on B-cells as suggested in this retrospective cohort study is conceivable. In addition, with the support by the role of DNMT1 in MDS and myeloid leukemia as reported in a previous review (40) and reports indicating a reduction in mRNA level of DNMTs by HDZ (37) and an abnormally high expression level of DNMTs in cell lines of MDS and myeloid leukemia including AML and CML (41), we suggest that HDZ alone may have enough efficacy to inhibit MDS or myeloid leukemia while previous trials selected a combination of HDZ and VAL (23,24,27,28).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A therapeutic significance of HDZ on B-cells as suggested in this retrospective cohort study is conceivable. In addition, with the support by the role of DNMT1 in MDS and myeloid leukemia as reported in a previous review (40) and reports indicating a reduction in mRNA level of DNMTs by HDZ (37) and an abnormally high expression level of DNMTs in cell lines of MDS and myeloid leukemia including AML and CML (41), we suggest that HDZ alone may have enough efficacy to inhibit MDS or myeloid leukemia while previous trials selected a combination of HDZ and VAL (23,24,27,28).…”
Section: Discussionsupporting
confidence: 77%
“…Over the last decade, several clinical trials have revealed that a combination of HDZ and VAL is a promising therapy for the several hematological malignancies, including mycosis fungoides (22), MDS (23,24), CTCL (25,26), AML (27), chronic myeloid leukemia (CML) (28). However, there has been no integral analysis targeting all the HNs as outcomes based on a large health insurance database.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible reasons behind this failure. For example, HDACi exert different outcomes depending on timing of administration and differentiation stage of the tumor (Kuendgen et al, 2011;Garcia-Manero et al, 2012;Novotny-Diermayr et al, 2012;Romanski et al, 2012;Xie et al, 2012;Candelaria et al, 2017;Huang and Zong, 2017;Young et al, 2017). In addition, the vast majority of preclinical and clinical studies deploying HDACi for anti-cancer treatment involved unselective inhibitors targeting all HDACs (pan-HDACi) with broad spectrum of side effects and toxicity, thus calling for exploitation of agents that specifically block individual HDACs.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of choice and dosage of the epidrugs was shown by the effect of the DNMT inhibitor hydralazine, exhibiting only mild effects in pharmacologically unreachable dosages despite good efficiency observed in other tumours. 7 , 8 A possible future limitation for epigenetic treatment in NETs could also be the observed non‐specific effect of increased renal uptake in our patients. Although changes in uptake measures of up to 25% SUV max between two scans have been described, 9 the increase in renal uptake was seen in 78% of our patients in the second PET/CT.…”
mentioning
confidence: 95%